Literasi fungsional bermuatan anti Kekerasan Berbasis Gender (KBG) di Kampung Bogor Kabupaten Manokwari Papua Barat - Yolanda Holle; Els Tieneke Rieke Katmo; Josina Waromi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Integrate gender base violence awareness into functional literacy learning program is aimed to develop modul about functional literacy contained gender base violence, conduct field study and applied modul of function literacy for Papuan women and men. This program is targeted community in Bogor sub district that consist og two neigboorhood groups, Bogor and Irmajaya. Most of the participant are farmers who lack of education. They commonly originated from Arfak and Biak. Learning method that used in this program is group-based approach, stakeholders’ incorporation in the program, role plays and colored picture and participatory approach. The result that will achieved from this program are integrated gender base violence in functional literacy modul that cultural appropriate. Four agents of change as pioner gender base violence awareness.